SUBMARINE FAN ENVIRONMENT INFERRED FROM TURBIDITE THICKNESS DISTRIBUTIONS - Carlson J.; Grotzinger J.P. (My University, 2001)
Recent studies of turbidite bed thickness distributions have demonstrated power-law as well as log-normal statistical distributions. The different distributions may reflect different fan processes and environments and, therefore, could be used as a quantitative method to help identify those environments, including those devoid of sequential patterns. The cumulative distributions of well-known turbidite deposits spanning a range of interpreted fan subenvironments are used to illustrate the potential correlation between cumulative distribution and environments. Assuming that power-law distributions may, for some systems, be the primary input signal, one-dimensional modelling allows semi-quantitative characterization of the effects of different fan processes such as erosion and bed amalgamation. Environments indicative of different fan processes may be characterized based on the degree to which processes have acted as a 'filter' to modify the assumed power-law distribution systematically. This model of the effect of fan processes on the power-law distribution is used to help to account for bed thickness distributions observed in several field sites.
Keywords: BED THICKNESS; DEBRIS FLOW; LOGNORMAL; POWER-LAW; SCALING; SUBMARINE FAN; TURBIDITE